MITIGATION OF METALLIC ION CONCENTRATIONS IN THE ENVIRONMENT USING MICROORGANISMS - Manoiu, Vasile-Sorin; Manoiu, Valentina-Mariana; Drugulescu, Manuel; Popa, Ovidiu (European Scientific Journal, ESJ, 2014)
Microorganisms, particularly bacteria, have the ability to bind and precipitate metals from different solutions, intracellularly or on the cell surface. An important application field of nanobiotechnologies is the mitigation of certain metals’ toxic effects by using microorganisms such as bacteria or yeasts. The product obtained through the microorganism activity is several times less toxic than the initial one. Bacillus subtilis is a bacterium that has the capacity of metal bioaccumulation. These bacteria can bioaccumulate Ag and Fe metallic ions from Ag and Fe ions solutions very rapidly. Microorganisms display large silver and iron based nanostructured deposits on the surface and in the immediate vicinity. Biosynthesis of silver and iron nanoparticles with the help of microorganisms is an ecological, viable, low cost, relatively easy and high-efficient method that allows the use of certain inexpensive biotechnologies for the metal absorption from the environment. This method can be tested for the metallic ions mitigation in the environment.